Stress dependence of dielectric properties in relaxor ferroelectrics: Monte Carlo investigation - Yongyut Laosiritaworn (2018)
In this work, we used Monte Carlo simulation to investigate the uniaxial stress dependence of the relaxor dielectric properties. The Metropolis algorithm and the spin glass type interaction were used in updating the local polarizations (representing the polar nano-regions). The exchange interaction in the spin glass Hamiltonian was assumed to be stress dependent via the strain. From the results, the frequency dependence of the dielectric permittivity were found, where, at high enough stress, the dielectric permittivity decreases with increasing stresses in qualitatively good agreement with experiments. In addition, from the modified Curie-Weiss law, all γ's stay close to 2. Therefore, this implies the frequency dispersion universality of the relaxor system under loading conditions. © (2010) Trans Tech Publications.